LTE network analysis in frequency reuse recycling techniques - Hussain, Muhammad Sabir; Suleiman, Nasri; Noordin, Nor Kamariah (Universiti Putra Malaysia Press, 2021)
In recent years, several researchers have embraced fractional frequency (FF) reuse as a strategy for resolving the inter-cell and co-channel interferences of adjacent cells (ICI, CCI) as the number of wireless networks grows. This technique is focused on the cell division of two parts, the inner and the outer, which enables multiple frequency bands to be assigned. The frequency advantages can be completely used in each inner zone, since there is no inter-cell disturbance for consumers in inner regions. According to this effective usage of the frequency spectrum available, FF will reduce the interruption of the channel and improve device efficiency. This manuscript presents a comprehensive study of different mechanisms to select the optimal FF scheme based on the user throughput. The analysis was conducted in order to obtain the optimal internal and external range for the cells as well as the optimal frequency distribution between the areas of the FR, Fractional Frequency Reuse 1 (FFR1) and Fractional Frequency Reuse 2 (FFR2) and evaluating their outputs and their number of users. In detail the overall consumer efficiency through the configured frequency distribution is analyzed. The FFR is a resource allocation technique that can effectively mitigate inter-cell interference (ICI) in LTE based HetNets and it is a promising solution. The proposal also employs high number sectors in a cell, low interference and good frequency reuse. The processes are tested by way of multiple modeling simulations.